The Effectiveness of the Supervisory Performance of the Algerian Parliament and the Bet Against Administrative Corruption - Hacene, Abderrazak; Aggoni, Mohamed (Journal of Legal Studies and Researches, 2021)
This study examines the role of parliamentary oversight in the fight against administrative corruption by promoting the values of integrity, transparency and accountability, at least legally. The study showed the diversity of parliamentary oversight mechanisms in the fight against administrative corruption, and revealed the limited effectiveness and the continuing widespread corruption phenomenon, because of a number of obstacles. The study concludes that it is difficult to hold Parliament alone to the inability of the effectiveness of its control activities and its inability to combat administrative corruption.